2016
DOI: 10.1016/j.actbio.2015.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial sprouting and network formation in collagen- and fibrin-based modular microbeads

Abstract: A modular tissue engineering approach may have advantages over current therapies in providing rapid and sustained revascularization of ischemic tissue. In this study, modular protein microbeads were prepared from pure fibrin (FIB) and collagen-fibrin composites (COL-FIB) using a simple water-in-oil emulsification technique. Human endothelial cells and fibroblasts were embedded directly in the microbead matrix. The resulting microbeads were generally spheroidal with a diameter of 100–200 μm. Cell viability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 70 publications
4
49
0
Order By: Relevance
“…80 Fibrin is used as a bioink for cell-loaded applications to support vascularization, but its bioactivity to support endothelial cell growth and proliferation may suggest its use for cell-free bioink formulations. 31, 39, 98 Because cell-free bioink depends on separate delivery of materials and cells, the use of this cell-free bioink may provide fabrication of “off-the-shelf” channeled scaffolds for later in vitro cell seeding or host tissue cellular integration.…”
Section: Cell-free Bioinkmentioning
confidence: 99%
“…80 Fibrin is used as a bioink for cell-loaded applications to support vascularization, but its bioactivity to support endothelial cell growth and proliferation may suggest its use for cell-free bioink formulations. 31, 39, 98 Because cell-free bioink depends on separate delivery of materials and cells, the use of this cell-free bioink may provide fabrication of “off-the-shelf” channeled scaffolds for later in vitro cell seeding or host tissue cellular integration.…”
Section: Cell-free Bioinkmentioning
confidence: 99%
“…Fibrin hydrogels can be seeded with cells and/or other molecular payloads – such as proteins, genes, or drugs - that aid in tissue regeneration [7]. In a conventional fibrin matrix, passive diffusion of the entrapped payload yields a burst release [8].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of materials and cell populations can be employed to engineer microtissues, depending on the application [1421]. For revascularization strategies, pure fibrin and composites made from fibrin, agarose, collagen, and gelatin have been used to develop engineered tissues capable of supporting endothelial vessel formation [2225]. …”
Section: Introductionmentioning
confidence: 99%
“…Past work by our group has shown that cell-encapsulating fibrin and collagen-fibrin microtissues can foster endothelial sprout formation and inosculation in a three-dimensional (3D) in vitro model [25, 26]. In particular, we have used co-cultures of endothelial cells and stromal cells to promote vessel formation in engineered tissues.…”
Section: Introductionmentioning
confidence: 99%